The moon of the moles - George, Jean Craighead. 1919-2012.; Levering, Robert, 1919- (New York : Crowell, 1969)
Describes the physical characteristics and habits of the mole who lives in underground tunnels and is busy throughout the four seasons.
Keywords: Moles (Animals) -- Juvenile literature; Moles (Animals) -- Kansas -- Juvenile literature; Moles (Animals)